Quando l’altro diventa sé. Zinaida Aleksandrovna Volkonskaja viaggiatrice d’Europa - Marta Valeri (eSamizdat)
The name of Zinaida Aleksandrovna Volkonskaya can be found in quite every memory of her contemporaries all over Europe. She was the daughter of prince Alexander Beloselsky-Belozersky, Catherine the Great’s ambassador. Grown up in Dresden, than in Turin, Zinaida left for Petersburg in her early adolescence, and after Napoleon’s defeat in the great patriotic war of 1812, followed the imperial entourage across Europe, took part in the Congresses of Vienna and Verona, fascinating Austrian, English, French and Vatican courts, establishing heartfelt and stimulating friendships with the most influential figures of her times, might they be politicians, intellectuals or artists. In Russia her name became famous thanks to her salon in Tverskaya street, in Rome she was well-known particularly for her patronage in support of the roman Russian artistic colony and, in the last days of her life, for her passionate support to catholicism. Her travel memories are different from those of anyone else because "To me it’s homeland, to you it’s a foreign country", as her personality was so influenced by her travel experiences to make her see in every journey an eternal return home.